Surgical management of sellar arachnoid cyst: state of the art and systematic review - Fabrizio, Michele Pio; Jannelli, Gianpaolo; Calvanese, Francesco; Delaidelli, Alberto; Cardia, Andrea; Momjian, Shahan; Manet, Romain; Jouanneau, Emmanuel; Milani, Davide (Frontiers in Neurology, 2025)
IntroductionSellar arachnoid cysts are rare intracranial lesions with variable clinical presentations, making their optimal management uncertain. This systematic review consolidates current knowledge on their epidemiology, radiological features, surgical management, and outcomes.Materials and methodsA literature search, following PRISMA-P 2015 guidelines, was conducted in MEDLINE/PubMed, Google Scholar, and Ovid Embase. Studies published in English from the year 2000 onwards were included. Data extraction focused on patient demographics, clinical presentation, surgical approaches, outcomes, and complications.ResultsThirty-three studies (16 case reports, 17 case series) met the inclusion criteria, encompassing 154 patients (59.34% female, mean age 51.48 years). The most common symptoms were visual disturbances (57.14%), headaches (35.06%), and endocrine disorders (30.52%). Surgical intervention details were available for 144 patients. Endoscopic transsphenoidal surgery was the most frequent approach (73.38%), followed by microscopic transsphenoidal surgery (11.69%). Various sellar reconstruction techniques were employed, including fascia lata, abdominal fat grafts, and nasoseptal flaps. The mean follow-up was 42.90 months. Postoperative complications occurred in 15.58% of cases, with cerebrospinal fluid leaks (7.14%) being the most common. Cyst recurrence was observed in 6.49% of patients. Most individuals with visual disturbances and headaches improved postoperatively, while endocrine function recovery was less consistent.Discussion and conclusionsSACs can cause significant morbidity due to mass effect and endocrine dysfunction. Endoscopic transsphenoidal surgery is the preferred treatment, but effective reconstruction is crucial to minimizing cerebrospinal fluid leaks. The recurrence rate highlights the importance of long-term follow-up. Future research should aim to standardize management protocols for improved outcomes.